Study about Brachial Plexus: Comprehension of Its Anatomy and Associated Injuries - Rajani Singh (Issues and Developments in Medicine and Medical Research Vol. 2, 2022)
Summary: Brachial Plexus formed by ventral rami of spinal nervers C5-T1, Occasionally C4 and T2 may contribute in the formation of brachial plexus. It gives rise to various motor and sensory nerves; median, ulnar, musculocutaneous, cutaneous nerves of arm and forearm etc innervating upper limb. These nerves may be injured by trauma and birth injuries causing different types of disability like erb’s palsy creating difficulties in carrying out day to day activities. Thus, aim of the study is to consolidate the information related to brachial plexus, how it is injured and what are their repercussions. To full this aim, literature survey was carried out using different data bases like scielo, pubmed, medline, researchgate etc. Various terms used for surfing were, brachial plexus, injuries of brachial plexus, significance of brachial plexus. Injury to erb’s point is mostly observed in childrens delivered by forceps delivery. The deformity is called erb’s palsy. Similary lower trunk, lateral and medial cord may be injured causing various type of deformities. Thus detailed knowledge of brachial plexus is of utmost use to neurosurgeongs to to detect the disability and correct the deformity.